Does proximity to the subventricular zone and expression of CXCR-4 and nestin affect prognosis in high-grade glioma?. (2nd November 2018) - Arzoglou, Vasileios; Tsitlakidis, Abraham; Foroglou, Nikolaos; Polyzoidis, Konstantinos; Makri, Styliani; Patsalas, Ioannis
Abstract: Background: It is suspected that infiltration of stem cell areas with high-grade glioma (HGG) generates a population that compromises treatment results and survival. In this prospective study we set to assess the prognostic value of the proximity of the contrast-enhancing lesion (CEL) on MRI to the subventricular zone (SVZ) and the expression of CXCR4 and nestin as potential factors in the stem cell migration pathway. Method: All patients diagnosed with high-grade glioma over a three-year period from a single institution were enrolled in this prospective study. Based on MRI preoperative findings, the patients were classified into 4 Groups (I–IV) according to the proximity of the CEL on MRI to the SVZ. Histological samples were assessed with immunohistochemistry for nestin and CXCR4. Classification into groups and the presence of nestin and CXCR4 were evaluated as predictive factors for overall (OS) and progression free survival (PFS). Results: Fourty patients were included in the study. In multivariate analysis, Groups II, III and IV predicted longer OS in comparison to group I ( p = 0.01; p < 0.01; p < 0.01 respectively) and group III and IV predicted longer OS in comparison to group II ( p < 0.01; p = 0.04 respectively). Group III predicted longer PFS than group I and II ( p = 0.01; p < 0.01 respectively). The expression rates of CXCR-4 and nestin could not predict OS or PFS. Conclusions: In our study the classification according to the proximity of the contrast enhancing part of the lesion and the SVZ proved to be prognostically significant for both OS and PFS. Presence of CXCR4 or nestin was not predictive for OS or PFS.